NIMG-37. DELAYED PSEUDOPROGRESSION IN TWO PATIENTS UNDERGOING TTFIELDS TREATMENT FOR NEWLY DIAGNOSED GLIOBLASTOMA. (9th November 2020) - Lowman, Allison; Hurrell, Sarah; Bobholz, Samuel; Connelly, Jennifer; Cochran, Elizabeth; Mueller, Wade; McGarry, Sean; Brehler, Michael; LaViolette, Peter
Abstract: PURPOSE: Tumor treatment fields (TTFields) are approved by the FDA for newly diagnosed as well as recurrent glioblastoma (GBM). TTFields have been shown to extend survival by 4.9 months in newly diagnosed GBM, and a landmark overall survival rate of 13% at 5 years. However, the specific effects remain widely unknown, which has prevented widespread clinical use of this treatment. METHODS: This case study examines two glioblastoma patients, IDH-1 wildtype, MGMT unmethylated, that received TTFields (Optune) in addition to maintenance temozolomide (TMZ) following radiation (RT). Both cases were followed using standard MR imaging. Second resections were performed due to radiographic progression of contrast enhancement. RESULTS: Although imaging was concerning for tumor progression, pathology showed only treatment effect, ultimately leading to the diagnosis of pseudoprogression. Both patients fell outside the normal expected timeline for chemo-radiation induced pseudoprogression. Based on the pathology, both patients resumed treatment with TMZ/TTFields. One patient expired at 25 months and one is still alive. CONCLUSIONS: Pathologic confirmation was essential for guiding further treatment and allowed patients to continue treatment that was effective despite contrary indications on imaging. These findings suggest that pathological confirmation should be strongly considered in patients receiving TMZ/TTFields who develop radiographic progression, potentially with a less invasive biopsy procedure. Future studies should look to characterize the underlying mechanism of interaction between TTFields/TMZ and quantify the prevalence, associated risk factors and whether there is a genotype more susceptible. Both patients reported here had O(6)-methylguanine-DNA methyltransferase (MGMT) unmethylated GBM, and while about 60% of glioblastomas are diagnosed likewise, it is possible that MGMT methylation status plays a role in TTFields response. Better characterization of this phenomenon will improve treatment guidance, potentially reducing unnecessary surgeries and the discontinuance of successful therapies.